Inherited Neuropathies - Fridman, Vera; Reilly, M. M. (Seminars in Neurology, 2015)
Hereditary neuropathies (HNs) are among the most common inherited neurologic disorders and are diverse both clinically and genetically. Recent genetic advances have contributed to a rapid expansion of identifiable causes of HN and have broadened the phenotypic spectrum associated with many of the causative mutations. The underlying molecular pathways of disease have also been better delineated, leading to the promise for potential treatments. This chapter reviews the clinical and biological aspects of the common causes of HN and addresses the challenges of approaching the diagnostic workup of these conditions in a rapidly evolving genetic landscape.
Keywords: hereditary neuropathy; Charcot-Marie-Tooth disease; hereditary sensory and motor neuropathy; hereditary sensory and autonomic neuropathy